Tính
a. 1 2 + 2 5 =
b. 3 4 - 2 3 =
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(1+\dfrac{3}{4}=\dfrac{7}{4}\)
b, \(\dfrac{4}{5}-\dfrac{3}{8}=\dfrac{32-15}{40}=\dfrac{17}{40}\)
c, \(1:\dfrac{2}{3}=\dfrac{1.3}{2}=\dfrac{3}{2}\)
d, \(\dfrac{2}{5}.\dfrac{5}{2}=1\)
8507cm2
32m^2 217dm^2=320217
3/5 giờ 12 phút = 48 phút
\(\dfrac{3}{7}.\left(\dfrac{5-1}{4}\right)=\dfrac{3}{7}.1=\dfrac{3}{7}\)
\(\dfrac{11}{10}-\dfrac{6}{10}=\dfrac{5}{10}=\dfrac{1}{2}\)
\(a,\dfrac{1}{3}-\left(-1\dfrac{2}{5}\right)+\left(-3\dfrac{1}{4}\right)\\ =\dfrac{1}{3}-\left(-\dfrac{7}{5}\right)-\dfrac{13}{4}\\ =\dfrac{1}{3}+\dfrac{7}{5}-\dfrac{13}{4}\\ =\dfrac{20}{3\times20}+\dfrac{7\times12}{5\times12}-\dfrac{13\times15}{4\times15}\\ =\dfrac{20+84-195}{60}\\ =\dfrac{-91}{60}\)
\(b,\dfrac{5}{4}-\left(-3\dfrac{1}{2}\right)-\dfrac{7}{10}\\ =\dfrac{5}{4}+\dfrac{7}{2}-\dfrac{7}{10}\\ =\dfrac{5\times5}{4\times5}+\dfrac{7\times10}{2\times10}-\dfrac{7\times2}{10\times2}\\ =\dfrac{25+70-14}{20}\\ =\dfrac{81}{20}\)
\(c,\dfrac{3}{2}-\left[\left(-\dfrac{4}{7}-\left(\dfrac{1}{2}+\dfrac{5}{8}\right)\right)\right]\\ =\dfrac{3}{2}-\left[-\dfrac{4}{7}-\left(\dfrac{4}{8}+\dfrac{5}{8}\right)\right]\\ =\dfrac{3}{2}-\left(-\dfrac{4}{7}-\dfrac{9}{8}\right)\\ =\dfrac{3}{2}+\dfrac{4}{7}+\dfrac{9}{8}\\ =\dfrac{3\times28}{2\times28}+\dfrac{4\times8}{8\times7}+\dfrac{9\times7}{8\times7}\\ =\dfrac{84+32+63}{56}\\ =\dfrac{179}{56}\)
`@` `\text {Ans}`
`\downarrow`
`a,`
\(\dfrac{1}{3}-\left(-1\dfrac{2}{5}\right)+\left(-3\dfrac{1}{4}\right)\)
`= 1/3+7/5 - 13/4`
`= 26/15 - 13/4`
`= -91/60`
`b,`
\(\dfrac{5}{4}-\left(-3\dfrac{1}{2}\right)-\dfrac{7}{10}\)
`= 5/4+7/2 - 7/10`
`= 1,25 + 3,5 - 0,7`
`= 4,75 - 0,7`
`= 4,05`
`c,`
\(\dfrac{3}{2}-\left[\left(-\dfrac{4}{7}\right)-\left(\dfrac{1}{2}+\dfrac{5}{8}\right)\right]\)
`= 3/2 - [(-4/7) - 9/8]`
`= 3/2 - (-95/56)`
`= 179/56`
\(a,\dfrac{4}{7}+\dfrac{7}{2}\\ =\dfrac{8}{14}+\dfrac{49}{14}\\ =\dfrac{8+49}{14}\\ =\dfrac{57}{14}\)
\(b,\dfrac{5}{8}\times\dfrac{3}{2}\\ =\dfrac{5\times3}{8\times2}\\ =\dfrac{15}{16}\)
\(c,\dfrac{3}{2}\times\dfrac{5}{6}-\dfrac{2}{3}\\ =\dfrac{3\times5}{2\times6}-\dfrac{2}{3}\\ =\dfrac{15}{12}-\dfrac{2}{3}\\ =\dfrac{15}{12}-\dfrac{8}{12}\\ =\dfrac{15-8}{12}\\ =\dfrac{7}{12}\)
\(d,\dfrac{13}{15}+\dfrac{2}{5}:\dfrac{3}{4}\\ =\dfrac{13}{15}+\dfrac{2}{5}\times\dfrac{4}{3}\\ =\dfrac{13}{15}+\dfrac{2\times4}{5\times3}\\ =\dfrac{13}{15}+\dfrac{8}{15}\\ =\dfrac{13+8}{15}\\ =\dfrac{21}{15}\\ =\dfrac{7}{5}\)
`1`
`a, 1/2 +1/3= 3/6 + 2/6 =5/6`
`d, 1/3 +3/5= 5/15 + 9/15=14/15`
`c,4/5 +1/2= 8/10 + 5/10= 13/10`
`2`
`a,1/2 +1/4=2/4 +1/4=3/4`
`b, 2/3 +1/6 = 4/6+1/6=5/6`
`c, 7/12 +1/2=7/12+ 6/12= 13/12`
`3`
Giải
Cả `2` ngày đi tất cả số quãng đường là :
`1/4 +1/2 =1/4+ 2/4= 3/4 ( quãng đường)`
đ/s...
`@ yL`
a) 3/7 + 3/4 - 1/2 =33/28-1/2=19/28
b) 6/11 + 2/9 x 12 =6/11+8/3=106/33
c) 5/7 - 8/5 : 4 =5/7-2/5=11/35
a) 3/7 + 3/4 - 1/2 = \(\dfrac{12}{28}+\dfrac{21}{28}-\dfrac{14}{28}=\dfrac{19}{28}\)
b) 6/11 + 2/9 x 12 = \(\dfrac{6}{11}+\dfrac{8}{3}=\dfrac{18}{33}+\dfrac{88}{33}=\dfrac{106}{33}\)
c) 5/7 - 8/5 : 4 = \(\dfrac{5}{7}-\dfrac{2}{5}=\dfrac{25}{35}-\dfrac{14}{35}=\dfrac{11}{35}\)
a: =20/60+12/60-15/60=17/60
b: =7/8-1/4-2/5=5/8-2/5=25/40-16/40=9/40
a: \(\left(\dfrac{3}{4}-81\right)\left(\dfrac{3^2}{5}-81\right)\cdot...\cdot\left(\dfrac{3^{2000}}{2003}-81\right)\)
\(=\left(\dfrac{3^6}{9}-81\right)\left(\dfrac{3}{4}-81\right)\cdot\left(\dfrac{3^2}{5}-81\right)\cdot...\cdot\left(\dfrac{3^{2000}}{2003}-81\right)\)
\(=\left(81-81\right)\left(\dfrac{3}{4}-81\right)\cdot\left(\dfrac{3^2}{5}-81\right)\cdot...\cdot\left(\dfrac{3^{2000}}{2003}-81\right)\)
=0
b: \(\dfrac{69}{157}-\left(2+\left(3+4+5^{-1}\right)^{-1}\right)^{-1}\)
\(=\dfrac{69}{157}-\left(2+\left(3+4+\dfrac{1}{5}\right)^{-1}\right)^{-1}\)
\(=\dfrac{69}{157}-\left(2+1:\dfrac{36}{5}\right)^{-1}\)
\(=\dfrac{69}{157}-\left(2+\dfrac{5}{36}\right)^{-1}\)
\(=\dfrac{69}{157}-\left(\dfrac{77}{36}\right)^{-1}\)
\(=\dfrac{69}{157}-\dfrac{36}{77}=\dfrac{-339}{12089}\)
a) Ta có: \(\dfrac{2}{\sqrt{3}-1}+\dfrac{3}{\sqrt{3}-2}+\dfrac{12}{3-\sqrt{3}}\)
\(=\dfrac{2\left(\sqrt{3}+1\right)}{2}-\dfrac{3\left(2+\sqrt{3}\right)}{1}+\dfrac{12\left(3+\sqrt{3}\right)}{6}\)
\(=\sqrt{3}+1-6-3\sqrt{3}+2\left(3+\sqrt{3}\right)\)
\(=-2\sqrt{3}-5+6+2\sqrt{3}\)
=1
b) Ta có: \(\dfrac{1}{\sqrt{3}-\sqrt{2}}-\dfrac{2}{\sqrt{7}+\sqrt{5}}-\dfrac{3}{\sqrt{5}-\sqrt{2}}+\dfrac{4}{\sqrt{7}+\sqrt{3}}\)
\(=\sqrt{3}+\sqrt{2}-\sqrt{7}+\sqrt{5}-\sqrt{5}-\sqrt{3}+\sqrt{7}-\sqrt{3}\)
\(=\sqrt{2}-\sqrt{3}\)
a . 1 2 + 2 5 = 5 10 + 4 10 = 9 10 b . 3 4 - 2 3 = 9 12 - 8 12 = 1 12
a, 12+25=37; b, 34-23=11